Analisis Tafsir Qur’an Surah Al-Isra Ayat 32 dan Jejaring Ayat Tentang Zina: Analysis of the Quranic Exegesis of Surah Al-Isra' Verse 32 and Related Verses Concerning Zina - Nasution, Labib Asshidqy (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The phenomenon of normalizing pre-marital relationships among Muslim youth, including dating practices and